Análises das terapias fotodinâmica, sonodinâmica e sonofotodinâmica para a inativação de biofilmes de candida albicans - Guimarães, Gabriela (2023)
Humanity has been plagued by infectious diseases throughout history and they remain one of the leading causes of death in the world. Fungal infections (FIs) represent an example of these emerging diseases, accounting for approximately 1.7 million deaths annually. The fungus Candida albicans can act as an opportunistic pathogen that has the ability to form biofilms as a resistance mechanism. C. albicans biofilms are resistant to antifungal agents, therefore, the search for alternative therapies that are able to inactivate biofilms is necessary. Alternative treatments arise, such as photodynamic inactivation (PDI), sonodynamic (SDI) and sonophotodynamic (SPDI). The present work analyzed PDI, SDI and SPDI, mediated by Curcumin as a photosensitizer in the inactivation of C.albicans biofilms, in addition, the work evaluated the role of ultrasound and light parameters in sonophotodynamic inactivation. Thus, the results showed that SPDI, PDI and SDI were able to reduce viability by 6.0; 1.2; 2.0 log, respectively, compared to the control biofilm. The results showed that with low doses of US, the effectiveness of the treatment decreases, and with higher doses, the effectiveness is greater, therefore, the US has a fundamental role in the effectiveness. The results also demonstrate that the use of light in combination with US is a promising alternative option to overcome limitations of PDI and SDI. These aspects reinforce and encourage the use and evaluation of SPDI for microbial diseases.